World History - Sandcastle Books (Sheriffs Lench Sandcastle Books, 2008)
An encyclopedia that covers all aspects of history from prehistory to now, with timelines, feature spreads, and illustrations.
Include Color Illustration
Keywords: World history -- World history -- Encyclopedias